Puke Ahu: articulating a place-based, university campus identity. (2nd January 2017) - Peace, Robin; Shearer, Fiona
ABSTRACT: Universities in Aotearoa New Zealand are public institutions established on lands purchased or acquired by government since 1869. As particular sites in the built landscape, they each carry a history and geography. A project at Massey University's Wellington campus seeks to open-up diverse identifications with the 'place' of the campus and has produced resources, established fora, and built relationships that differently recognise aspects of place and identity. The Pākehā authors reflect on the theoretical frameworks that have influenced their work on the project including geography, critical pedagogy, and discourse theory. As Pākehā academics engaging with the indigenous history of the land through which they work, the authors discuss the implications of this knowledge and the difficulties and responsibilities of working in a project that seeks emancipatory outcomes.